Fused Deposition Modeling (FDM) 3D Printing of the Thermo-Sensitive Peptidomimetic Drug Enalapril Maleate - Lena Hoffmann; Jörg Breitkreutz; Julian Quodbach (MDPI AG, 2022)
Fused deposition modeling (FDM) 3D printing was used to produce 3D printed tablets with the thermo-sensitive model peptidomimetic drug enalapril maleate (EM). Two different formulations were prepared to investigate the degradation of enalapril maleate during the FDM 3D printing process. Soluplus® and Eudragit® E PO were chosen as polymers. After hot-melt extrusion (HME) and FDM 3D printing, both formulations were characterised regarding their solid-state properties using DSC and XRD. The degradation of the drug was analysed by determination of the content in the extrudates and 3D printed tablets, and dissolution was assessed. Various approaches have been attempted to prevent degradation of enalapril maleate, including utilization of a larger nozzle diameter and higher printing speeds to reduce heat exposition. None of these approaches were successful in preventing drug degradation. However, significant differences in the amount of degradation between the two formulations with different polymers could be observed. Thus, the FDM 3D printing process was not feasible without any degradation for the thermo-sensitive drug enalapril maleate. A maximum of 85.55 ± 1.48% enalapril was recovered in Eudragit® E PO tablets printed with a 0.4 mm nozzle at a temperature of 180 °C and with a speed of 30 mm/s.